THE EFFECT OF DOUGH PREPARATION METHODS USING BEET JUICE ON THE QUALITY INDICATORS OF WHITE FLOUR BREAD - S. N. Yedygova; Z. N. Khatko; Z. R. Jolov (Новые технологии, 2022)
The article considers the possibility of using beet juice in the production of white flour bread. The use of beetroot juice in the recipe will not only enrich the product with vitamins, minerals, dietary fiber, pectin, fiber, but also improve and make the appearance of the product noticeable.The purpose of the research is to study the technology of white flour bread production with the addition of table beet juice.The tasks are the following: to substantiate the use of beet juice in the technology of wheat bread; to investigate the effect of beet juice on the lifting power of baker's yeast; to determine the effect of beet juice on the quality indicators of wheat bread; to develop a technical and technological map for white flour bread with the addition of beet juice.To evaluate raw materials, semi-finished products and finished products, modern methods of analysis have been used to determine the chemical composition, nutritional and biological value, physicochemical and organoleptic characteristics of the samples under study. Trial baking was carried out on the basis of the Maikop State Technological University at the Department of Food Technology and Catering, the Faculty of Agricultural Technologies. To knead the dough, a blend of juices obtained from Bordeaux and Krasny shar beet varieties was used. The dough was prepared using straight dough method, long straight dough method and sourdough methods. In the course of the study, a positive effect of table beet juice on the technological properties of the dough, the lifting power of yeast, as well as the quality of the finished bread was established. The use of juice during kneading has shown an acceleration of the lifting force of the yeast and an improvement in its technological properties.